Printability, Mechanical and Thermal Properties of Poly(3-Hydroxybutyrate)-Poly(Lactic Acid)-Plasticizer Blends for Three-Dimensional (3D) Printing - Kontárová, Soňa; Přikryl, Radek; Melčová, Veronika; Menčík, Přemysl; Horálek, Matyáš; Figalla, Silvestr; Plavec, Roderik; Feranc, Jozef; Sadílek, Jiří; Pospíšilová, Aneta (Materials (Basel, Switzerland), 2020)
This paper investigates the effect of plasticizer structure on especially the printability and mechanical and thermal properties of poly(3-hydroxybutyrate)-poly(lactic acid)-plasticizer biodegradable blends. Three plasticizers, acetyl tris(2-ethylhexyl) citrate, tris(2-ethylhexyl) citrate, and poly(ethylene glycol)bis(2-ethylhexanoate), were first checked whether they were miscible with poly(3-hydroxybutyrate)-poly(lactic acid) (PHB-PLA) blends using a kneading machine. PHB-PLA-plasticizer blends of 60-25-15 (wt.%) were then prepared using a corotating meshing twin-screw extruder, and a single screw extruder was used for filament preparation for further three-dimensional (3D) fused deposition modeling (FDM) printing. These innovative eco-friendly PHB-PLA-plasticizer blends were created with a majority of PHB, and therefore, poor mechanical properties and thermal properties of neat PHB-PLA blends were improved by adding appropriate plasticizer. The plasticizer also influences the printability of blends, which was investigated, based on our new specific printability tests developed for the optimization of printing conditions (especially printing temperature). Three-dimensional printed test samples were used for heat deflection temperature measurements and Charpy and tensile-impact tests. Plasticizer migration was also investigated. The macrostructure of 3D printed samples was observed using an optical microscope to check the printing quality and printing conditions. Tensile tests of 3D printed samples (dogbones), as well as extruded filaments, showed that measured elongation at break raised, from 21% for non-plasticized PHB-PLA reference blends to 84% for some plasticized blends in the form of filaments and from 10% (reference) to 32% for plasticized blends in the form of printed dogbones. Measurements of thermal properties (using modulated differential scanning calorimetry and oscillation rheometry) also confirmed the plasticizing effect on blends. The thermal and mechanical properties of PHB-PLA blends were improved by the addition of appropriate plasticizer. In contrast, the printability of the PHB-PLA reference seems to be slightly better than the printability of the plasticized blends.
Keywords: plasticizers; biodegradable polymeric blends; poly(hydroxybutyrate)-poly(lactic); printability; citrates; poly(ethylene glycol) PEG; 3D printing